Case Report: Siblings with neonatal lupus erythematosus - Tang, Pengyue; Zhang, Huan; Li, Ping (Frontiers in Pediatrics, 2025)
Neonatal lupus erythematosus (NLE) is a rare autoimmune disorder characterized by cutaneous and/or cardiac manifestations resulting from the transplacental passage of maternal antibodies, including anti-SSA/Ro, anti-SSB/La, and occasionally anti-U1RNP. This report describes two siblings with distinct NLE presentations, emphasizing the importance of early diagnosis and management, particularly in light of the rising rates of multiple births. A 15-day-old girl (Case 1) presented with classic annular skin lesions and strongly positive SSA and SSB antibodies. Six years later, her brother (Case 2) developed atypical red papules with similar serologic findings. Their mother, diagnosed with Sjögren's syndrome after the first child's (Case 1) presentation, demonstrated suboptimal treatment adherence, which may have contributed to the occurrence of NLE in her second child (Case 2). Neither sibling exhibited systemic involvement, including cardiac manifestations; however, regular monitoring remains essential. These cases highlight the variable NLE phenotype, even within families. In pregnancies with SSA/SSB antibody positivity, close monitoring of antibody titers, electrocardiograms (ECGs), and echocardiograms is paramount for early NLE detection and optimal management, especially given inconsistent maternal treatment. These cases underscore the need for heightened vigilance and proactive strategies in high-risk pregnancies.